Northward expansion of the bivoltine life cycle of the cricket over the last four decades. (4th October 2018) - Matsuda, Naoki; Tanaka, Kazuhiro; Watari, Yasuhiko; Shintani, Yoshinori; Goto, Shin G.; Nisimura, Tomoyosi; Izumi, Yohei; Numata, Hideharu
Abstract: Recent climate warming has affected some life‐history traits of insects, including voltinism and body size. The magnitude of changes in these traits may differ latitudinally within a species because of the differing lengths of season available for growth. The present study aims to estimate the change in voltinism of the lawn ground cricket, Polionemobius mikado (Shiraki) (Orthoptera: Trigonidiidae), over the last four decades by comparing the body size between adults collected from a wide range of latitudes in Japan in recent years (2015–2017) and those collected four decades ago (1969–1976). The body size of adults collected in recent years showed a latitudinal saw‐tooth cline, in the same way as body size did four decades ago, and the cline shifted northward over the last four decades: In 2015–2017, the body size decreased slightly with increasing latitude from 31°N to 36°N, and then increased to 40°N, and again decreased from 40°N to 44°N. Comparison of the body size between recent years and four decades ago revealed that the body size has decreased significantly at the middle latitudes (36–40°N), suggesting that the proportion of smaller bivoltine individuals there has increased over the last four decades. The sum of effective temperatures for postdiapause embryonic development at around 36°N in recent years was comparable to that at 31–35°N four decades ago, at which P. mikado populations were bivoltine. Taken together, these findings suggested that the latitudinal range suitable for the bivoltine life cycle of P. mikado has expanded northward over the last four decades because of climate warming. This is the first report that shows that a decrease in body size can be caused by climate warming via an increase in voltinism. Abstract : The body size was compared between adults of Polionemobius mikado collected from wide ranges of latitudes in Japan in recent years and those collected four decades ago, and the results showed that the body size had decreased significantly at the middle latitude. The length of the growing season at the middle latitude in recent years was comparable to that at lower latitudes four decades ago, where P. mikado populations were bivoltine. These findings suggested that the latitudinal range suitable for the bivoltine life cycle has expanded northward over the last four decades because of climate warming.